Maintenance management of local authorities asset / Muhammad Mohd Said - Mohd Said, Muhammad (Faculty of Architecture, Planning and Surveying, 2009)
This thesis aims is to evaluate the effectiveness of maintenance management of local authorities asset. The emphasis to the effectiveness of maintenance management needed is important because if asset users feel uncomfortable for their asset will impact directly to the government delivery system and national development. Besides that, the objective of this study also to make comparisons between 3 units of local authorities in Selangor based on 3 main aspect of maintenance management systems: aspect of methods and policies of maintenance that apply, human resources planning aspect, and financial aspect. Apart from making comparison, equation and conflict between the 3 local authorities also will be evaluated on this thesis based on 3 main aspect of maintenance management. Data and results which obtain from this study get from the circulation of questionnaire to the asset consumer and also from structural questionnaire which use to interviews the maintenance management of local authorities party.